The mechanisms of parasite clearance after antimalarial treatment of Plasmodium falciparum malaria. - Chotivanich, K; Udomsangpetch, R; Dondorp, A; Williams, T; Angus, B; Simpson, J; Pukrittayakamee, S; Looareesuwan, S; Newbold, C; White, N (2000)
Studies were conducted to determine how malaria parasites are cleared from the blood after antimalarial treatment. Neither artesunate nor quinine decreased parasitized red cell deformability or increased antibody binding. In acute falciparum malaria, ring-infected erythrocyte surface antigen (RESA) was observed in erythrocytes without malaria parasites (RESA-red blood cell [RBC]), indicating prior parasitization. In uncomplicated malaria, RESA-RBC numbers increased significantly (P=.002) within 24 h of starting artesunate but rose much more slowly (7 days) after quinine treatment. In severe malaria, RESA-RBC increased significantly (P=. 001) within hours of starting artesunate but not with quinine treatment (P=.43). RESA-RBCs were not produced after drug treatment of malaria parasite cultures in vitro. Rapid malaria parasite clearance after treatment with artemisinin derivatives results mainly from the extraction of drug-affected parasites from host erythrocytes-presumably by the spleen. This explains why the fall in hematocrit after treatment of hyperparasitemia is often less than that predicted from loss of parasitized cells.